2021
DOI: 10.3389/fcvm.2021.666465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Atrial Appendage Closure in Combination With Catheter Ablation on Left Atrial Function for Persistent Atrial Fibrillation

Abstract: Background: A single procedure combining left atrial appendage closure (LAAC) plus catheter ablation (CA) has been proven to be safe and feasible for treating atrial fibrillation (AF). However, the influence of treatment modality on left atrial (LA) function is not thoroughly explained.Objective: We aimed to investigate the changes of LA function in persistent AF patients undergoing concomitant LAAC and CA.Methods: The study population comprised 65 patients who underwent combined AF ablation and Watchman LAAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A total of 247 articles were screened from a comprehensive electronic database search. After thorough review, we found 8 retrospective or prospective observational studies (one of them was only published as an abstract) that evaluated the LA function after LAAC 12–19 . The search process is detailed in (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 247 articles were screened from a comprehensive electronic database search. After thorough review, we found 8 retrospective or prospective observational studies (one of them was only published as an abstract) that evaluated the LA function after LAAC 12–19 . The search process is detailed in (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Leave‐one‐out analyses were performed to detect any influential effects of the included studies, especially those with the highest contribution to heterogeneity. Total atrial emptying fraction (TAEF): Yang et al 13 was the study of most contribution to heterogeneity. Omitting Yang et al 13 dropped I 2 from 75% to 31% without significant changes to the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) How do the ablation and the LAAC interact with each other in the combined procedure? Several small sample studies including a randomized study demonstrated consistent results that the additional LAAC did not to influence the success of AF ablation [16 23,31]. However, the impact of AF ablation on LAAC is contradictory.…”
Section: Important Issues and Future Directionsmentioning
confidence: 97%